Longitudinal Changes in Whole-Brain Functional Connectivity Strength Patterns and the Relationship With the Global Cognitive Decline in Older Adults - Li, Qiongge; Dong, Chao; Liu, Tao; Chen, Xiaodan; Perry, Alistair; Jiang, Jiyang; Cheng, Jian; Niu, Haijun; Kochan, Nicole A.; Brodaty, Henry; Sachdev, Perminder S.; Wen, Wei (Frontiers in Aging Neuroscience, 2020)
Aging is associated with changes in brain functional patterns as well as cognition. The present research sought to investigate longitudinal changes in whole brain functional connectivity strength (FCS) and cognitive performance scores in very old cognitively unimpaired individuals. We studied 34 cognitively normal elderly individuals at both baseline and 4-year follow-up (baseline age = 78±3.14 years) with resting-state functional magnetic resonance imaging (r-fMRI), structural MRI scans and neuropsychological assessments conducted. Voxel-based whole brain FCS was calculated and we found that bilateral superior parietal and medial frontal regions showed decreased FCS, while the supplementary motor area (SMA) and insula showed increased FCS with age, along with a decrease in bilateral prefrontal cortical thickness. The changes of FCS in left precuneus were associated with an aging-related decline in global cognition. Taken together, our results suggest changes in FCS with aging with the precuneus as a hub and this may underlie changes in global cognition that accompany aging. These findings help better understand the normal aging mechanism.